18 Hypoxia-driven Hand1 expression controls changes in cardiac metabolism around birth. Issue 24 (24th November 2011) - Breckenridge, R A; Neary, M T; Bennett, M; Kotecha, S; Griffin, J; Mohun, T J
Abstract : Little is known about the changes occurring in the heart at birth. Immediately following birth, cardiac output rapidly increases, and to facilitate this, the predominant mode of cardiac energy generation shifts from glycolysis to Î 2 -oxidation of lipid. This is relevant to adult cardiac failure, as energy metabolism in failing hearts shifts back to glycolysis. Currently, control of cardiac energy substrate selection is incompletely understood. The b-HLH transcription factor Hand1 has been implicated in cardiac development, and levels of Hand1 RNA are altered in several types of cardiac failure associated with metabolic remodelling. Here we show that cardiac Hand1 RNA levels fall rapidly after birth, directly in response to changes in cardiac hypoxia signalling. Prevention of the postnatal fall in cardiac Hand1 transcription in transgenic neonates results in a lethal phenotype of cardiac rupture. We observe alterations in gene expression, cardiac acyl-carnitine metabolism and overall lipid metabolism consistent with reduced fatty acid mitochondrial import. We speculate that Hand1 transcription is regulated by hypoxia signalling and thus link ambient oxygen concentration to metabolic substrate selection. This is a novel function for Hand1, which has been implicated in control of development of the heart, placenta and neural tube-all processes that are known to be in some way influenced by hypoxia signalling.